Understanding plant-microbe interactions and their impact on plant-host stress resilience through the lens of multi-omics - Kazarina, Anna (My University, 2025)
While the implications of plant-microbe interactions are well-established, significant knowledge gaps remain in understanding how plants shape microbial communities and how these microbes affect plant performance. My dissertation explores the role of plants' local adaptation through microbial recruitment and plant–microbe communication using various methods, from broad community fingerprinting to integrated multi-omics. My first study evaluated the relative importance of plant genetic background and environmental factors in shaping rhizosphere bacterial communities, using the perennial C4 grass Andropogon gerardii as a model. Employing a reciprocal garden experiment across a sharp precipitation gradient with distinct regional ecotypes, I characterized ecotypic rhizosphere communities using 16S rRNA amplicon sequencing. The results showed that abiotic conditions and the local soil microbes were the primary drivers of community composition. However, the plant ecotypic effect was also significant, highlighting active microbial recruitment driven by plant genetic background. Interestingly, plants grown at their native sites were more successful at recruiting location-unique microbes, supporting the “home-field advantage” hypothesis. These unique microbes may represent microbial specialists linked to plant stress responses. Additionally, ecotype-specific recruitment of congeneric but genetically distinct bacterial variants highlighted the fine-scale influence of host genotype on rhizosphere microbiome assembly. The second study builds on the first one and explores potential mechanisms of “home-field advantage.” Using gene-centric and genome-centric metagenomic approaches, I investigated the functional potential of root-associated bacteria and their genetic capacity to support plant stress resilience. I also profiled plant metabolic products that may govern rhizosphere recruitment and are potentially produced in response to plant-microbe interactions. Findings suggested that plants adapted to drier environments experience less stress, producing fewer stress-related metabolites while recruiting microbes with genes linked to stress alleviation. Notably, plant-derived trimethyllysine was highly associated with microbial populations that improve nutrient uptake, promote plant growth, and modulate stress responses. The third study switches focus to validation and application, exploring the enhancement of plant-host resilience through the creation of a plant-oriented SynCom. Using culturomics, I single-cell sorted and cultured microbes from rhizosphere soils and assembled their draft genomes. I then evaluated their potential communication and beneficial functional potentials, as well as provided insights into the microbial metabolites. The results revealed that bacterial isolates from both arid and wet environments have the potential to positively influence plant growth, resilience, and support other microbes through the exchange of signaling molecules and metabolic products. Notably, arid-environment isolates produced distinct metabolites associated with stress tolerance and support of plant growth under drought conditions, including lyso-phosphatidylethanolamine 17:1 (LPE 17:1). While the exact function of LPE 17:1 is unknown, I hypothesized that it could enhance the plant host’s tolerance to drought stress through priming the host immune system. This dissertation advances our understanding of the complex factors influencing plant adaptation to local environments. Furthermore, it sheds light on the mechanisms underlying plant-microbe communication, rhizosphere recruitment, and the complex interactions within the holobiont system, offering a foundation for future research.
Keywords: Plant microbiome; Local adaptation; Precipitation gradient; Muti-omics; Culturomics